Alienation of Black College Students on White Campuses: University-Centered and Student-Centered Interventions - Doneida A. Cook (Educational Considerations, 1990)
Recommendations are presented for both university-centered and student-centered interventions for the problems of adjustment due to alienation of Black students on White campuses.